Factors influencing fruit and vegetable intake among urban Fijians: A qualitative study. (1st June 2016) - Morgan, E.H.; Vatucawaqa, P.; Snowdon, W.; Worsley, A.; Dangour, A.D.; Lock, K.
Abstract: Low fruit and vegetable intake is an important risk factor for micronutrient deficiencies and non-communicable diseases, but many people worldwide, including most Fijians, eat less than the World Health Organization recommended amount. The present qualitative study explores factors that influence fruit and vegetable intake among 57 urban Fijians (50 women, 7 men) of indigenous Fijian (iTaukei) and South Asian (Indian) descent. Eight focus group discussions were held in and around Suva, Fiji's capital and largest urban area, which explored motivation for eating fruit and vegetables, understandings of links to health and disease, availability and sources, determinants of product choice, and preferred ways of preparing and eating fruit and vegetables. Data were analysed using thematic content analysis. Regardless of ethnicity, participants indicated that they enjoyed and valued eating fruit and vegetables, were aware of the health benefits, and had confidence in their cooking skills. In both cultures, fruit and vegetables were essential components of traditional diets. However, increasing preferences for processed and imported foods, and inconsistent availability and affordability of high-quality, low-priced, fresh produce, were identified as important barriers. The findings indicate that efforts to improve fruit and vegetable intake in urban Fijians should target the stability of the domestic fruit and vegetable supply and access.